Abundance and Harvest of Caulerpa racemosa (lato) at Siquijor Island, Central Visayas, Philippines - Calumpong, Hilconida P. (Silliman Journal, 2024)
The abundance and harvest of edible Caulerpa racemosa at Siquijor Island, central Philippines, were surveyed. The C., racemosa community occupied an area of about 0.9 km? (90 ha), where 13 families harvest a total of 60 baskets daily, each weighing (wet) 30-40 kg and selling at P8,00/basket. The area yields an annual harvest of 21,900 baskets (657,000-876,000 kg wet weight) valued at a minimum of P175,200. Greatest values for standing crop and biomass (0.734 kg/m?; 1.123 kg/m? wet weights) were taken from depths ot 0.5 to 1.0 m in the. lower intertidal, approximately 160 m from shore, where the substrate was mud.